Tinjauan Singkat Konstitusi Tertulis yang Pernah Berlaku di Indonesia - Haryanti, Dewi (Jurnal Selat, 2014)
The Constitution contains the main rules that guarantee the rights of citizens from arbitrary actions rather than the ruler and the implementation of community interest. There is a written Constitution and there are unwritten. Constitution is the constitution tertulis.Negara Indonesia has three written constitution. The written constitution of Indonesia, namely the Constitution of 1945 (UUD 1945) applies padatanggal August 18, 1945 until December 27, 1949), which consists of 16 Chapters and 37 Articles, the Constitution of the Republic of Indonesia (RIS Constitution or the Constitution of 1949) or The Constitution also called RIS dated December 27, 1949 - August 17, 1950 consists of 6 chapters and each chapter consists of several sections, Constitution while 1950 (Provisional Constitution / Constitution 1950) dated August 17, 1950 - July 5, 1959 consists of 6 chapters and each chapter consists of several sections. On July 5, 1959 President Sukarno issued a decree that dissolved the constituent assembly and declared void 1945. In May 1988, there were reforms that have an impact on the changes (amendments) to the 1945 Constitution. The first amendment dated October 19, 1999, both dated August 18, 2000, the third of November 9, 2001, and the fourth date of August 10, 2002. As the embodiment of the aspirations of the people who are less satisfied with the amendments, the Assembly established a "Constitutional Commission" assigned to conduct a comprehensive assessment of the 1945 changes. Keywords: Review, Written Constitutions, in Indonesia